Optimalisasi Pekarangan Rumah Dengan Budidaya Sayuran Sebagai Alternatif Pangan di Pedesaan - Putro, Tetuko Rawidyo; Sistriatmaja, Muhammad Bagus; Lukman Hakim; Mulyanto; Siti Aisyah Tri Rahayu; Riwi Sumantyo; Hery Sulistyo Jati; Johadi; Ariyanto Adhi Nugroho; Muhammad Yusuf Indra Purnama (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
Food security and economic empowerment of rural communities are key challenges in sustainable development. Utilizing home gardens for vegetable cultivation can increase food availability, reduce dependence on external food sources, and improve community economic well-being. This community service activity aims to improve community skills in food production, family income, and the technical (hard skills) and social (soft skills) skills of participants through the use of home gardens. The study was conducted in Sumber Village, Sumber District, Rembang Regency, from August 2024 to February 2025. Methods included outreach, training, mentoring, and evaluation. Data were collected through observation, interviews, and pre- and post-tests with program participants. Program implementation showed a 40% increase in vegetable production within six months. Pre- and post-test evaluations showed a significant increase in hard skills (cultivation techniques and organic fertilizer utilization) by 35% and soft skills (communication and cooperation) by 30%. This program has been proven to improve food security, family income, and community skills. This model can be replicated in other areas with a similar approach, and further strategies are needed for program sustainability.